Morphological variation and genetic diversity of Circinaria contorta (Megasporaceae, Ascomycota), including C. contorta subsp. albida subsp. nov. - Katarzyna Szczepańska; Beata Guzow-Krzemińska; Justyna Sołtysiak; Jacek Urbaniak (Scientific Reports)
Abstract Circinaria contorta is a widely distributed, crustose, saxicolous lichen, which thallus is composed of olive-brown, white pruinose areoles and crater-like apothecia. Although it is one of the more common taxa occurring on limestone substrata in Europe and a generic type species, no type specimen has ever been designated for this species, and there are only a very few studies concerning this taxon. During research on C. contorta in Poland, tree main phenotypes (groups A, B and C) were delineated within the sampled material. Molecular analyses of sequences of the genus Circinaria from worldwide sampling indicated that representatives of C. contorta did not form one clade but rather were distributed at different points within the phylogenetic tree, probably due to difficulties in the correct identification of this species. Analyses based on three molecular markers, namely nucITS rDNA, MCM7, and mtSSU rDNA sequences, showed that specimens representing the phenotypic groups A and C were intermixed on the phylogenetic tree within the C. contorta group. However, the specimens from group B formed a separate, well-supported clade and are described herein as a new taxon at subspecies rank, Circinaria contorta subsp. albida. Specimens of group C had phenotypic features similar to those of Circinaria hoffmanniana, suggesting that the taxonomic concept of this species needs clarification. Furthermore, the species concept of Circinaria contorta subsp. contorta has been specified by designating an epitype specimen collected in Germany. This specimen belonged to phenotypic group A and contained aspicilin as a secondary metabolite.